Connection between Matrimony and Family - Dumbliauskas, Vytautas (Problemos, 1987)
The group matrimony has replaced promiscuity but has not produced family. The latter has originated only on the base of pair matrimony as the cell for care and education of children. Matrimony and family were at first closely linked together. Later they have separated themselves. Two factors have led to this result. Firstly, the breeding of children has overstepped the bounds of matrimony, thus producing a non-matrimonial family. Secondly, children have ceased to make a necessary component of matrimony. As a result, the modem connection between matrimony and family has got looser. Matrimony not necessarily leads to a family as a breeding group, and the outset of a family not necessarily must coincide with a marriage. In a traditional family (parents plus children) the connection between matrimony and family may acquire the form of the opposition between the right of parents not to live with an unloved partner. That is, the right of divorce and the right of children to live with both parents.